Erodability of Stabilised Pavements Using the Wheel Tracking Test - Yeo, Yang sheng; Jitsangiam, Peerapong; Nikraz, Hamid (Australian Geomechanics Society, 2011)
An estimated total of $1.5 billion dollars is spent on road rehabilitation in Australia per annum. This invokes a sustainabile urgency to ensure reasonable service life is achieved for pavements. Cement treated basecourse provides a strong support to the pavement and is deemed as an alternate solution to reduce maintenance requirements of unsealed roads whilst minimising the generation of dust. When cemented basecourses are used for unsealed roads, its promary purpose it often to maintain serviceability in lieu of sustaining heavy traffic loads, thus the vulnerability to erosion dictates its service life. In Australia, the study of erosion due to tyre loading on cemented pavements and its testing methodology thereof are very limited. The Cooper Wheel Tracking Test typically used for asphalt rutting testing is carried out to determine the Erodibility Index of cement treated crushed rocks. Results indicate that the increase in cement content increases the Erodibility Index. A proposed testing methodology for stabilised basecourse is ultimately derived from the investigation.